IMPROVING STUDENTS’ READING COMPREHENSION ON DESCRIPTIVE TEXT THROUGH RECIPROCAL TEACHING TECHNIQUE - Heryuningsih, Chelsy; Sutapa Y, Y. Gatot; Wardah, Wardah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research was conducted in order to solve the problem encountered in the classroom; the students were passive in learning process, they also had difficulties to figure out the main idea, supporting details, and determine the synonym and antonym. The method of the research was classroom action research. The subject of this research was the tenth grade students science V of SMA Negeri 7 Pontianak in Academic Year 2017/2018. When the researcher applied the reciprocal teaching technique, the students began to show their interests by actively answering the questions and enthusiasm in having their roles in learning process. The result of this research showed that reciprocal teaching did not only improve the students? reading comprehension, but also the students? interaction between the students to students and the students to the teacher. Key Words: Reading Comprehension, Reciprocal Teaching, Descriptive Text